Study of the magnitude of premenstrual syndrome in a tertiary care institute in Pondicherry, India - Varghese, Jessy; Koothan, Vijaya; Sujaritha, V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Premenstrual syndrome is cyclical physical and behavioural symptoms that appear in days preceding menstruation and interfere with work or life style followed by a symptom free interval. The common affective and somatic symptoms seen are mood swings, irritability, anxiety, breast tenderness, weight gain and abdominal bloating. The present study was done to detect premenstrual syndrome and encourage students to seek treatment which would improve quality of life both socially and academically. Methods: A cross-sectional study was conducted over a period of three months from November 2018 to January 2019 among medical students in a tertiary care institute in Pondicherry. A detailed questionnaire regarding premenstrual symptoms and screening for depression was obtained from all study subjects. Diagnosis of premenstrual syndrome was done if there were at least one affective symptom like mood swings, insomnia, anxiety and one somatic symptom like abdominal bloating, breast complaints and weight gain. Results: Total of 207 students were screened out of whom 155 (74.87%) students were found to have premenstrual syndrome. 41 students did not have the same, 11 students were excluded as they were having endocrine disorders like polycystic ovarian syndrome and thyroid abnormalities. 60.6% had mild 38.4% moderate 4.5% had severe premenstrual syndrome. Commonest symptoms were mood swings 81.9% followed by anxiety 80% and fatigue 71.6% breast complaints and joint pains were seen in 71% equally so also abdominal bloating and weight gain which was seen in 67%. Depression was found in 52.9% of the students. Conclusions: Premenstrual syndrome is prevalent among medical students commonly and detecting it and encouraging students to seek treatment will help them perform better socially and academically.